Effectiveness of an Education Program on Nurses Knowledge toward Enteral Nutrition Support for Unconscious Patients at Critical Care Unit in Imam Al-Hussein Medical City in Holy Karbala - Haitham Ibrahim Faris, Rajaa Ibrahim Abed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Critically patients in the intensive care unit can suffer from malnutrition, which can have an adverse impact on patient outcomes. Nutrition, including enteral nutrition (EN), is largely neglected in clinical practice. As a result, dangers and safety issues for patients and healthcare professionals may arise. Objectives: to Measure the Effectiveness of an Educational Program on Nurses Knowledge toward enteral Nutritional Support for Unconscious Patients Methods: A quasi-experimental was conducted at the Critical Care Unit in Imam AL-Hussein Medical City in Holy Karbala for the period of November 24th, 2020 to April 27th, 2022. A non-probability "purposive sample" of (60) nurses who are working at critical care unit . the sample divided into two groups, control group consist of (30) nurses and study group consist of (30) nurses exposed to the nursing educational program. Data were collected by using Self-administered questionnaire form relevant to the nurses' knowledge and demographic data Results: The study's findings indicate that the study group's knowledge of enteral nutrition support for unconscious patients in critical care units is greater to that of the control group at the post-test, as compared to the control group's knowledge , so the educational program was effective in increasing nurses' knowledge. Conclusion: After a post-test for a study group on Nutritional Support for Unconscious Patients, there was an increase in nurses' knowledge. In comparison, the control group did not show any progress in their knowledge of Nutritional Support for Unconscious Patients at the pre and post-test. Recommendation: Special and long continuing educational program should be established and applied for nurses who are working in intensive care units concerning Nutritional Support for Unconscious Patients , and Work on the principle of reward and punishment in the application the guidelines of nutritional support in intensive care units.